Up-Front and Salvage Transoral Laser Microsurgery for Early Glottic Squamous Cell Carcinoma: A Single Centre Retrospective Case Series - Meulemans, Jeroen; Bijnens, Jacqueline; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Oncology, 2018)
Introduction/aim: Transoral laser microsurgery (TLM) is a minimally invasive surgical alternative for radiotherapy in the primary management of early glottic cancer. More recently, TLM emerged also as a possible salvage treatment for selected radiorecurrent cancers. We reviewed outcomes of primary and salvage TLM performed in a Belgian tertiary referral center. Patients and methods: A retrospective review of records from 142 consecutive patients who underwent TLM was performed. Oncologic outcomes were evaluated by means of descriptive statistics and Kaplan-Meier estimates. Variation of estimated outcomes between different subgroups was evaluated using log-rank analysis. Results: Of 142 patients, 109 (76.8%) underwent TLM as a primary treatment and 33 (23.2%) were treated in a salvage setting for recurrent or second primary glottic cancer. cT classification in the up-front TLM group was cT1a in 72 (66.1%), cT1b in 11 (10.1%) and cT2 in 26 (23.9%) patients. In the salvage group, patients were cT/rT classified as cT1a-rT1a in 17 (51.5%), cT1b-rT1b in 1 (3.0%), cT2-rT2 in 14 (42.4%) and cT3-rT3 in 1 (3.0%) patients. All patients were cN0. Second look TLM was performed in 28 patients (19.7%) and radiotherapy was associated as adjuvant therapy in 5 patients (3.5%). Mean follow-up was 51.6 months (SD=38.4 months). Three-year overall survival (OS) was 94.1% (SE=2.2%), 3-year disease specific survival (DSS) 100%, 3-year disease free survival (DFS) 80.1% (SE=3.8%), 3-year local recurrence free survival (RFS) 81.0% (SE=3.7%) and 3-year ultimate local control rate with laser alone 89.2% (SE=3.0%). Upon subgroup analysis, no differences in OS, DSS and DFS were observed between the up-front and salvage group (log rank; p=0.306, p=0.298, p=0.061 respectively). However, local RFS and ultimate local control rate with laser alone were significantly higher in the primary treated TLM group (log rank, p=0.014 and p=0.012). Five-year laryngeal preservation rate was 89.7% (SE=3.5%) in the total population, 100% in the upfront group and 64.9% (SE=9.8%) in the salvage group, a difference which proved statistically significant (Log-Rank, p<0.001) Conclusion: This retrospective study confirms excellent oncologic outcomes of up-front TLM for early glottic cancer. In the salvage setting, TLM allows avoidance of total laryngectomy in the majority of cases.